Universal Mass-Energy Equivalence Relation is Expressed by Mechanical Energy of a Falling Body on Earth at Constant Acceleration Due to Gravity - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2024)
In this research article, it is shown that a falling body on earth at constant acceleration due to gravity will also exhibit the universal mass-energy equivalence relation given as dE/E = dm/m, when the energy considered is mechanical energy. Total mechanical energy is the sum of the potential and kinetic energies.